كمبوديا 50 عاما من بناء السلم الاجتماعي والهرب من أشباح الخمير الحمر - د.فؤاد الغزيزر .; مأسمدي سأعأ . (TAWASUT, 2022)
ملخص:عانت بعض الأقليات المسلمة في جنوب شرق آسيا من العداء الشيوعي ضـد الإسلام والمسلمين، ومارست الأنظمة الشيوعيـة ولا تزال الهجمات الإلحـادية والإبادة الجماعية ضد الأقليات المسلمـة في بعض بلدان آسـيـا، وإن كـانت آثار الحقبـة الشيوعيـة مازالت باقـيـة فـي النفوس، وفي الحـيـاة الاجتماعية والاقتصادية والثقافية.وتعتبر مملكة كمبوديا نموذجا لتلك الأقليات التي عانت من مذابح الإبادة الجماعية التي ارتكبها الخمير الحمر في سبعينيات القرن العشرين.وتتناول هذه الدراسة موضوع: "كمبوديا 50 عاما من بناء السلم الاجتماعي والهرب من أشباح الخمير الحمر"، حيث تعرض هذا البلد لأبشع إبادة جماعية لردح من الزمن، سعى خلالها المجتمع الدولي إلى إحلال السلام في تلك المنطقة، توجت تلك الجهود بتوقيع اتفاقيّة باريس للسلام أو ما تعرف باتفاقيّة كمبوديا الشاملة للسلام عام 1991م.الكلمات المفتاحية: كمبوديا، الخمير الحمر، الإبادة الجماعية، السلم.AbstractSome Muslim minorities in Southeast Asia suffered from communist hostility against Islam and Muslims, and communist regimes were practiced and atheistic attacks and mass extermination against Muslim minorities are still in some countries of Asia, although the effects of the communist era still remain on the souls, and also in social, economic and cultural life.The Kingdom of Cambodia is considered as a model for those minorities that suffered from the genocide committed by The Khmer Rouge  in the 1970s.This study deals with the topic: « “Cambodia is 50 years of building social peace and escaping from the ghosts of The Khmer Rouge (the suffering of the homeland», as this country was shown to the most heinous genocide for a period of time, during which the international community sought to bring peace to that region, these efforts culminated in the signature of The Paris Peace Agreement or what is known as the Cambodia Comprehensive Peace Agreement of 1991.Key words: Cambodia, The Khmer Rouge, genocide, peace.